Antibacterial activity of some selected brands of Malaysian honey - Tumin, Norizah (2004)
Honey is an ancient remedy for the treatment of infected wounds, which has recently been 'rediscovered' by the medical profession, particularly where conventional modern therapeutic agents are failing. Honey is made up of simple sugars and is an excellent source of energy. It is hypertonic and sterile with antibacterial activity against many pathogenic bacteria. The present study aims to investigate the antibacterial activities of five different brands of Malaysian honey. 'Tualang', 'Hutan' and 'Gelang' honey are produced from wild bee, 'Pucuk Daun' and 'Ee Feng Gu' honey are from honeybee farm were considered for this study. Six different pathogenic bacteria, E. coli, S. typhi, S. sonnei, P. aeruginosa, S. aureus and S. pyogenes were selected as test organisms. Diluted and neat honeys were used for the antibacterial assay. Solvent extraction of honey was carried out with an aim to isolate the active principle behind the antibacterial property. MIC of the selected honey was determined. 'Tualang' honey was found to be most effective against S. typhi. It also showed a substantial antibacterial activity against E. coli and S. pyogenes. 'Hutan' and 'Gelang' honey does not show any antibacterial activity against the organism tested. 'Pucuk Daun' honey showed antibacterial activity E. coli and S. sonnei. 'Ee Feng Gu' was active against E. coli, S. typhi, S. sonnei and S. aureus. Among the solvent extracts only acetone fraction showed antibacterial activity. Extracts with petroleum ether, chloroform and ethyl acetate does not show any activity. The MIC (Minimum Inhibitory Concentration) values of 'Pucuk Daun', 'Gelang' and 'Hutan' honey were 5.0 IJQ/ml, 17.5 IJQ/ml and 28.75 IJQ/ml respectively against S. sonnei.